Statelessness and Migration in the Turkish System - Şeker, Güven; Ökmen, Mustafa (Border Crossing, 2025)
This research discusses the legal structures and policy interventions in Turkey related to the phenomenon of statelessness. In this context, individuals do not have citizenship and encounter serious obstacles in accessing fundamental rights and services. Situated at the intersection of Europe and Asia, Turkey receives enormous migration influxes, further complicating the issues of statelessness. The nation has enacted laws to recognize and protect stateless individuals, providing them with identity documents that grant access to essential services like health and work. However, systemic discrepancies, administrative tardiness, and low public knowledge impede the effective social integration and equal treatment of these individuals. The study contrasts 19 key Turkish legal texts with international law and academic commentary to determine how much Turkey’s approach aligns with international norms. Although Turkey has ratified the 1954 Convention on Statelessness, it has yet to accede to the 1961 Convention, including its prevention provisions, specifically for children born to stateless individuals. This is putting large numbers of individuals, among them Syrian refugees, in a position of legal limbo. The study recommends that Turkey ratify the 1961 Convention, ease the procedures for ascertaining statelessness, enhance education campaigns on the rights of stateless persons, and develop comprehensive strategies for addressing the root causes. By embracing best practices from around the world and strengthening its legal framework, Turkey has the potential to become a leader in combating statelessness and ensuring equitable treatment for all individuals subject to its jurisdiction.